Latent Tuberculosis is Highly Prevalent in Sub-Saharan Africans in Dublin - a Study Intended to Establish Normal CD4 Reference Ranges in this Population - Bates, Killian (Trinity Student Medical Journal, 2004)
Objectives: To establish the normal reference range for CD4 lymphocyte cells in human immunodeficiency virus (HIV) negative sub-Saharan Africans attending the Genito-Urinary and Infectious Diseases (GUIDE) Outpatient Clinic at St. James’s Hospital in Dublin. To correlate CD4 Count with lymphocyte count. Design: This was a prospective observational study. Methods: Volunteers were recruited among new sub-Saharan African patients attending the GUIDE Outpatient Clinic at St. James’s Hospital, Dublin. Recruitment took place over an eight-week period between July and August 2003. The study objectives and methods were explained to volunteers, and informed consent for participation was obtained. History and relevant physical examination, together with measurement of haematological parameters, screening for sexually transmitted infections (STIs) and examination of stool and urine samples were performed to exclude confounding co-morbidities. A chest radiograph and Mantoux skin test was performed to exclude pulmonary tuberculosis (TB). Results: Seventeen participants were recruited. Two (12%) were excluded on the basis of HIV infection. Ten men and five women form the CD4 study group. Of the fifteen suitable patients recruited, the range of CD4 count is 532–1537 x 106/L. The reference range used by the laboratory at St. James’s, based on CD4 counts in largely Caucasian populations, is 380 – 1500 x 106/L. Despite a high level of coincidental findings in the cohort, the range of CD4 counts measured falls within the range currently used by the laboratory. Women had significantly higher CD4 cell counts than men (median = 1245 and 899 respectively. P < 0.01), as has been previously described. There was a strong linear relationship between CD4 cell count and absolute lymphocyte count (r2=0.5). Twelve of thirteen patients (92%) screened had evidence of latent pulmonary tuberculosis (TB), on the basis of a positive Mantoux reaction without radiographic evidence of TB. Two of fifteen (13%) HIV-negative patients defaulted before the result of their tuberculin skin test could be read. Only one patient in the entire cohort had a negative reaction to tuberculin challenge. We have referred 92% of this cohort for tuberculosis chemotherapy. Conclusions: The range of CD4 lymphocyte counts measured in this cohort falls within that used by the central pathology laboratory at St. James’s Hospital, and by clinicians at GUIDE. This is the range that is used to guide clinical care among HIV-positive patients at GUIDE. A high rate of latent TB exists in this cohort.